Planejamento de um sistema de gestão de energia elétrica - Estudo de caso: UTFPR - Câmpus Medianeira - Souza, Pedro Henrique Rossi de (2017)
The increase in the gap between supply and demand for energy coupled with the depletion of natural resources together highlighted the need to search for alternatives that could mitigate these problems. Since then, policies, programs and laws have been created with the aim of promoting energy efficiency in the most diverse segments. In this context, a Brazilian Association of Technical Standards has issued an ISO 50001: 2011 NBR Standard, an energy management system, including an energy planning procedure. In this way, the present work aimed to implement the planning process of an electric power management system at the Universidade Tecnológica Federal do Paraná – Câmpus Medianeira, based on the requirements established by ISO 50001: 2011, in view of the need for combat The increase in consumption and demand for electricity. At the entrance of the planning, correlation tests were carried out in order to verify and interpret an influence of non-consumption temperature and electric power demand. An energy review was then carried out by analyzing the billing history, as well as the history of consumption and energy demand. Even at this stage, the areas with significant energy use and the points of despair due to the use of air conditioning were identified. In the phase out of the planning an energy baseline was established through forecasting models. In the sequence, performance indicators were established and finally a plan of action with the purpose of contributing to the future energy performance of the consumer unit.